Sposoby kształcenia w grafice książkowej w wyższym szkolnictwie artystycznym Krakowa i Warszawy w Polsce Ludowej (1945-1952) - Boguszewska, Anna (Biuletyn Historii Wychowania, 2019)
The purpose of the study is to present the principles of education in the field of book art as part of applied graphics, provided at the Academies of Fine Arts in Krakow and Warsaw. These two academic environments stimulated revival of this type of education. The analysis pertains to 1945–1952 when Poland witnessed crucial political and ideological changes affecting a new character of education. In the study, the process of nationalisation of artistic education is presented. The author shares her assumptions of the new teaching curricula designed in accordance with the ideological needs of the communist authorities. Marxism-Leninism was taught as a foreground subject. Graphic departments were established to educate specialists to be employed by the state propaganda. An attempt has been made to reconstruct the personal composition of the graphic faculties lecturers in both academic centres.